The hunger report. - Alan Shawn Feinstein World Hunger Program (Providence, R.I., U.S.A. Alan Shawn Feinstein World Hunger Program, Brown University, 1988)
Annual
Keywords: Food supply -- Periodicals; Famines -- Periodicals; Food relief -- Periodicals; Poor -- Periodicals; Hunger -- Periodicals